Auxin-mediated biosynthesis of silver nanoparticles: comprehensive characterisation and antibacterial activity analysis - Sahil; Chaudhary, Anis Ahmad; Sorout, Sonia; Yadav, Kushi; Ali, Mohamed A. M.; Boufahja, Fehmi; Kumar, Vikram; Kothari, SL; Jain, Devendra; Verma, Kumar Sambhav (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundSilver nanoparticles (AgNPs) are well-known for their potent antibacterial properties. However, the rise of antibiotic-resistant bacteria highlights the need for alternative antimicrobial strategies. Green synthesis using biological molecules offers an eco-friendly route to nanoparticle production.ObjectiveThis study aims to synthesise AgNPs using plant growth hormones (Auxins), specifically indole-3-acetic acid (IAA) and indole-3-butyric acid (IBA), and to evaluate their antibacterial activity against pathogenic bacteria.MethodsAgNPs were synthesised using IAA and IBA as reducing and stabilising agents. The synthesised nanoparticles were characterised by UV-Visible spectroscopy, Fourier Transform Infrared Spectroscopy (FTIR), Particle Size Analysis, Dynamic Light Scattering (DLS) for hydrodynamic diameter, Zeta potential for surface charge, and Field Emission Scanning Electron Microscopy (FE-SEM) for morphological analysis. Antibacterial assays were performed against Staphylococcus aureus and Escherichia coli.ResultsThe IAA and IBA-mediated AgNPs showed controlled size distribution, stability, and uniform morphology. Enhanced antibacterial activity was observed, particularly against S. aureus, compared to E. coli.ConclusionIAA and IBA-mediated synthesis provide a green, sustainable method for producing AgNPs with significant antibacterial potential. These Auxin-based AgNPs represent promising candidates for combating antibiotic-resistant bacterial strains.